Corak Sufistik dalam Tafsir Fayd Ar-Rahman - Hafid Nur Muhammad; Dudung Abdul Karim; Dais Hajjar Fauziyah (Program Studi Ilmu Al-Quran dan Tafsir STIU Darul Quran, 2022)
Various approaches taken by the commentators in interpreting the Qur'anhave been attempted, including the Sufi approach as written by Sholeh Darat. Thispaper aims to describe the Sufistic style contained in the book of Fayd Ar-Rahmanby Sholeh Darat. The method used in this research is the library method which iscarried out by reviewing the literature related to the discussion theme. The result ofthis research is that Sholeh Darat is a Sufistic scholar who gave birth to the firstcommentary work in the archipelago in Javanese (Arabic pegon). interpretation canenrich the treasures of interpretation of the archipelago.